Science education in Europe: national policies, practices and research (Luxembourg, 2011)
"The study examines the organisation of science teaching in Europe and provides an overview of existing policies and strategies that aim at improving and fostering science teaching and learning today. It looks at support measures available to teachers and schools for boosting students' motivation and interest in science. The study also contains a literature review on science education, main findings from the international surveys PISA and TIMSS as well as results from a Eurydice pilot survey (SITEP) on the content of initial teacher education programmes. It covers 31 countries (all EU Member States, plus Iceland, Liechtenstein, Norway and Turkey) and takes the reference year 2010/11. "